Field-based thermal performance analysis of a cement-stabilized, core-insulated rammed earth house in a cold climate - Harvey, Gabriel; Szentesi-Nejur, Szende (Frontiers in Built Environment, 2025)
This study presents an exploratory, in-depth case study on the short-term thermal and hygrothermal performance of a cement-stabilized, core-insulated rammed earth house in a cold-climate region of eastern Canada. Rammed earth construction is increasingly promoted as an eco-efficient solution for winter-dominated climates due to its thermal and moisture-regulating properties, however, empirical validation under real-world conditions remains limited. A three-day monitoring campaign was conducted under free-running winter conditions using three complementary methods: infrared thermography (IRT), surface heat flux sensing, and in-situ temperature and humidity measurements. The results reveal measurable thermal lag, reduced diurnal temperature swings, and delayed heat dissipation during unheated periods, indicating high passive heat retention. IRT demonstrated dynamic surface temperature responses to solar exposure, particularly on the south-facing wall, while heat flux data confirmed reduced transmittance through the composite earthen envelope. Indoor temperature and relative humidity remained stable throughout the monitoring period, reflecting effective hygrothermal buffering. Although limited in duration and scope, this study provides a rare, high-resolution benchmark dataset that characterizes the short-term behavior of insulated rammed earth walls in cold climates and supports future simulation-based and long-term field investigations.